Identification of Misconception Using Diagnostic Tests: Systematic Literature Review - Ditya Lufita; Heru Kuswanto; Dadan Rosana; Ficha Aulia Indah Pratiwi; Lucy Triananda (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to review studies that use diagnostic tests to identify misconceptions in physics learning and examine the methods used to overcome them. The results of the review can be used by educators in choosing the type of diagnostic test and method to overcome misconceptions. The methods used are PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and content analysis. A total of 50 articles published in 2018–2023 were analyzed, which focused on the development of diagnostic tests and the application of methods to overcome misconceptions. The results of the study indicate that misconceptions can be identified through various forms of diagnostic tests, such as two-tier, three-tier, four-tier, five-tier, six-tier, and multiple-choice tests. In addition, an educational computing-based approach or computer-assisted learning has proven effective in overcoming misconceptions, especially when supported by the right learning process and model.